Vínculos afectivos en niños, niñas y adolescentes pertenecientes a hogares sustitutos del municipio de Sevilla Valle (2021)
The author who supported this research was Bowlby, (1976); this is of a phenomenological nature, with a descriptive scope, from a qualitative point of view in which 2 children and 2 adolescents participated; the category was Affective bonds, the subcategories were the types of bonds: Secure attachments, Avoidant insecure attachments, ambivalent insecure attachments and disorganized attachments with the respective sub-categories. The results showed that the typology found to a greater extent in children and adolescents was secure attachments. On the other hand, the one with the least number of findings was the typology of disorganized relationships, which probably indicates that the relationships of the four participants from a general point of view are not associated as such with any type of psychopathology